Curriculum Contextualization Analysis: Alignment of Learning Materials with The Socio-Cultural Needs of Early Childhood - Agis Wulandari; Hajerah Hajerah; Andi Yuliani Suras; Zalsabhila Zahwa Rajuni; Nurfilzah Maharani (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Curriculum contextualization in early childhood education is the process of aligning learning materials and experiences with the students' socio-cultural backgrounds to make learning more relevant and meaningful. This study aims to examine the alignment of learning material characteristics with the students' socio-cultural contexts, describe the implementation of local culture in instruction, identify challenges faced by the school, and analyze the findings through the perspectives of the sociology and anthropology of education. A qualitative approach with a case study design was employed at the Alea Play Group and Kindergarten in Makassar. Data collection involved observations and semi-structured interviews with the school principal, teachers, and parents, conducted from May 4 to 7, 2026. The results indicate that learning materials have been adapted to the students' socio-cultural contexts by fostering habits of politeness, discipline, and cooperation, utilizing the environment as a learning resource, and involving parents. The school also integrates local culture that aligns with Islamic values, such as proper conduct, mutual respect, responsibility, and care for others. Challenges encountered include a lack of local culture-based learning media, suboptimal parental involvement, and the need for enhanced teacher competence. Drawing on Pierre Bourdieu’s theory of Cultural Capital and George D. Spindler’s anthropology of education, this study concludes that spiritual alignment with local culture creates more meaningful learning experiences for young children.